Acessibilidade ao patrimônio documental da Universidade Federal de Santa Maria - a disponibilização das atas do Conselho Universitário (1961-1964) - Retamoso, Lívia Regina Rocha (2013)
Access to files is usually delimited physically due to the distance between the query environments and research. Thus arose the need, within the community in general, the documentation for one of the Governing Bodies of the University , the University Council, the highest body of collective deliberation for administrative issues and defining the general policy of UFSM. The overall goal of this research is to provide accessibility to the meeting minutes of the Board of the Federal University of Santa Maria, the period from 1961 to 1964, through the Information Technology and Communication (ICT), in order to provide and universalize documentary heritage and History of this institution, through a descriptive catalog on paper and electronically. Specifically, we shall show the composition and functioning of the Governing Bodies of UFSM, emphasizing the University Council; establish a description of the documentation in the study by the Brazilian Standard for Archival Description (NOBRADE); contribute to the preservation of documentary heritage UFSM as well as its institutional History, scan the minutes of the University Council in order to maximize their access, providing the survey instrument - catalog - the internet through the ICA - ATOM software; prepare a descriptive catalog of the Minutes of the University Council in support paper and in electronic media, providing quality access to archival information, with a view to publication and effective via software Ica - Atom. This dissertation is, literally, an introductory statement, with the first part including an approach to documentary heritage in the context of cultural heritage; in the second part, access, accessibility and use of information technologies and communication; in the third part, contextualizes the Federal University of Santa Maria; in the fourth part, archival description; the farm part of the methodology; on sixth, the results, ire the catalog of the Proceedings of the 1st to the 46th Session of the University Council of UFSM and lastly, final remarks. When finished, have to say that the Catalogue, the object of this study is available at www.ufsm.br/patrimonioarquivistico.